1990
DOI: 10.1523/jneurosci.10-04-01062.1990
|View full text |Cite
|
Sign up to set email alerts
|

The lateral amygdaloid nucleus: sensory interface of the amygdala in fear conditioning

Abstract: Previous work has implicated projections from the acoustic thalamus to the amygdala in the classical conditioning of emotional responses to auditory stimuli. The purpose of the present studies was to determine whether the lateral amygdaloid nucleus (AL), which is a major subcortical target of projections from the acoustic thalamus, might be the sensory interface of the amygdala in emotional conditioning. Lesions were placed in AL of rats and the effects on emotional conditioning were examined. Lesions of AL, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
586
0
6

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,016 publications
(640 citation statements)
references
References 38 publications
38
586
0
6
Order By: Relevance
“…Thus, we would like to speculate that enhanced amygdaloid processing in the basolateral complex, possibly due to a failure in inhibition, may account for enhanced fears (Isoardi et al, 2004;Rodriguez Manzanares et al, 2005) and lead to a reduction in social interactions. This is supported by a rodent study showing that lesioning the BLA, the main relay station for fear associations, impaired not only fear conditioningFa well established finding (LeDoux et al, 1990)Fbut also led to an increase, rather than a decrease, in social interactions (Woolley et al, 2006). Thus, it is conceivable that an overly active and plastic amygdala may produce enhanced anxiety and fear processing, leading to social withdrawal to avoid aversive, fear-evoking exposure.…”
Section: Indirect Effects Of Non-amygdala Regionsmentioning
confidence: 70%
See 1 more Smart Citation
“…Thus, we would like to speculate that enhanced amygdaloid processing in the basolateral complex, possibly due to a failure in inhibition, may account for enhanced fears (Isoardi et al, 2004;Rodriguez Manzanares et al, 2005) and lead to a reduction in social interactions. This is supported by a rodent study showing that lesioning the BLA, the main relay station for fear associations, impaired not only fear conditioningFa well established finding (LeDoux et al, 1990)Fbut also led to an increase, rather than a decrease, in social interactions (Woolley et al, 2006). Thus, it is conceivable that an overly active and plastic amygdala may produce enhanced anxiety and fear processing, leading to social withdrawal to avoid aversive, fear-evoking exposure.…”
Section: Indirect Effects Of Non-amygdala Regionsmentioning
confidence: 70%
“…To explore the possible cellular and synaptic changes in the amygdala of the VPA animals, we performed in vitro slice electrophysiological experiments on the LA, the sensory relay station between the aversive shock and the conditioned tone stimulus (LeDoux et al, 1990), and examined how pyramidal neurons (Figure 4a) responded to stimulation of the amygdala and how synaptic connections reacted to a Hebbian pairing protocol.…”
Section: In Vitro Slice Electrophysiology In the Basolateral Amygdalamentioning
confidence: 99%
“…It has previously been demonstrated that basolateral/lateral amygdala is predominantly involved in fear learning, while the central and medial parts form the output of the amygdala, with major projections to the hypothalamus and brain stem regions (Kopchia et al 1992;LeDoux 1992;LeDoux et al 1990). Therefore, in addition to controlling fearinduced suppression of behavior, the serotonergic input to the amygdala may also be involved in fear learning, an aspect which will warrant further study.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial amount of evidence supports the notion that the amygdala is a key brain structure in the modulation of emotional behavior (Davis, 1992;LeDoux, 2000;Davis, 1997;Fendt and Fanselow, 1999;Maren, 1999) and particularly in pavlovian aversive learning (LeDoux et al, 1990;Gewirtz and Davis, 1997;Miserendino et al, 1990;Fanselow and Kim, 1994). It is known that the basolateral complex (BLA) receives relevant information from the environment via hippocampal, thalamic, and cortical afferents (McDonald, 1998;Davis and Whalen, 2001).…”
Section: Introductionmentioning
confidence: 96%